Theoretical Overview of Discrete Choice Experiment - Czine, Péter (International Journal of Engineering and Management Sciences, 2020)
The purpose of this study is to present a preference evaluation method, the discrete choice experiment. The reader can gain information on the background, application areas (with particular emphasis on health economics), the process and about three models (multinomial logit, random parameter logit, nested logit). Based on the results of literature analysis it can be said that the method is very promising, but in many areas it still needs improvement.